2019
DOI: 10.1038/s41598-019-56756-6
|View full text |Cite
|
Sign up to set email alerts
|

The degradation of organic compounds impacts the crystallization of clay minerals and vice versa

Abstract: Expanding our capabilities to unambiguously identify ancient traces of life in ancient rocks requires laboratory experiments to better constrain the evolution of biomolecules during advanced fossilization processes. Here, we submitted RNA to hydrothermal conditions in the presence of a gel of Al-smectite stoichiometry at 200 °C for 20 days. NMR and STXM-XANES investigations revealed that the organic fraction of the residues is no longer RNA, nor the quite homogeneous aromatic-rich residue obtained in the absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 44 publications
3
12
0
Order By: Relevance
“…Interestingly, we identified a decrease of the NH 3 + component (at 401.6 eV) and an increase of the NH 2 contribution (at 400.2 eV) in both samples, being more noteworthy in the gly-acNon pellet. Previous works have shown that Al-smectites and Mg-smectites favored the accumulation of N-rich organic residues after exposing ANR under hydrothermal conditions 28,29 . In our experiments, the fact that the fragmentation of the glycine molecule (mainly driven by decarboxylation) and the increment of the NH 2 / NH 3 ratio are more noteworthy in the acid-treated sample, might also indicate that glycine photodegradation produces an enrichment of amino-rich moieties over the samples, as previously suggested by Tzvetkov et al 44 .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Interestingly, we identified a decrease of the NH 3 + component (at 401.6 eV) and an increase of the NH 2 contribution (at 400.2 eV) in both samples, being more noteworthy in the gly-acNon pellet. Previous works have shown that Al-smectites and Mg-smectites favored the accumulation of N-rich organic residues after exposing ANR under hydrothermal conditions 28,29 . In our experiments, the fact that the fragmentation of the glycine molecule (mainly driven by decarboxylation) and the increment of the NH 2 / NH 3 ratio are more noteworthy in the acid-treated sample, might also indicate that glycine photodegradation produces an enrichment of amino-rich moieties over the samples, as previously suggested by Tzvetkov et al 44 .…”
Section: Discussionmentioning
confidence: 94%
“…These results are consistent with the work of Vinogradoff et al 30 that showed that the starting compositional nature of phyllosilicates (Al vs Fe-rich) strongly determines the chemical evolution of organic matter in asteroids. On the other way around, recent investigations have also revealed the influence of post-depositional hydrothermal alteration in the preservation of organic compounds in smectites and on the final mineral assemblages 28,29 . All these works highlight the importance of studying in detail the nature of the host minerals and their chemical evolution as the key to improve the searching for traces of life beyond Earth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These chemical variations cannot be due to post-depositional mineralogical effects. In fact, although distinct mineral phases will not impact similarly the thermal degradation of organic molecules 17,[21][22][23][24]26,46 , the BRC organic films investigated are only associated to microquartz (Figs. 1 and 3).…”
Section: Discussionmentioning
confidence: 96%
“…Although the general perception in paleobiology has long been that thermal maturation processes lead to a converging composition of organic materials from different origins 7 , several studies have demonstrated that organic molecules may undergo only partial degradation during their geological history [8][9][10][11][12][13][14][15] . In parallel, laboratory experiments have evidenced that burial-induced thermal degradation processes may not completely obliterate organic geochemical signals [16][17][18][19][20][21][22][23][24][25][26] and have suggested that initial organic molecular heterogeneities can withstand diagenesis and be recognized in the fossil record 27 .…”
mentioning
confidence: 99%